P-values indicating the relationships among affiliation network position metrics (based on positive GAIs) and strategies of behavior, habitat use, and site fidelity in the population of humpback whales in the Kitimat Fjord System. - Janie Wray (457395); Eric Keen (11014169); Éadin N. O’Mahony (11014172) (2021)
P-values indicating the relationships among affiliation network position metrics (based on positive GAIs) and strategies of behavior, habitat use, and site fidelity in the population of humpback whales in the Kitimat Fjord System.